Responding to COVID-19 crisis: effectiveness of HR implementation, a contrast between essential and non-essential sector in Malaysia - Lim, Chee Yoong (2021)
The COVID-19 pandemic is a crisis that has greatly impacted the business environment. To contain the disease from spreading further, Malaysia had declared a Movement Control Order (MCO) where every citizen has to stay at home unless there is a valid reason. This cause many businesses to struggle to stay afloat during the pandemic.